2017
DOI: 10.1186/s12889-017-4324-6
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs, illness perceptions and determinants of breast screening uptake in Malta: a cross-sectional survey

Abstract: BackgroundWomen’s beliefs and representations of breast cancer (BC) and breast screening (BS) are salient predictors for BS practices. This study utilized the health belief model (HBM) and common-sense model (CSM) of illness self-regulation to explore factors associated with BS uptake in Malta and subsequently, to identify the most important predictors to first screening uptake.MethodsThis cross-sectional survey enrolled Maltese women (n = 404) ages 50 to 60 at the time of their first screening invitation, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
45
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 75 publications
15
45
1
2
Order By: Relevance
“…A higher proportion of respondents (70.5%) in this study correctly identified the symptoms of breast cancer presented to them while fewer (50%) correctly identified risk factors for the cancer depicting partial knowledge of breast cancer among the respondents. These findings are consistent to those of Morse et.al (20) in Tanzania and Marmara et.al (21) in Malta who found variations in both knowledge of symptoms and breast cancer risk factors. The sources of information mentioned in this study included the electronic media (radio and television) and hospitals similar to findings of a review by Ojewusi et.al, (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A higher proportion of respondents (70.5%) in this study correctly identified the symptoms of breast cancer presented to them while fewer (50%) correctly identified risk factors for the cancer depicting partial knowledge of breast cancer among the respondents. These findings are consistent to those of Morse et.al (20) in Tanzania and Marmara et.al (21) in Malta who found variations in both knowledge of symptoms and breast cancer risk factors. The sources of information mentioned in this study included the electronic media (radio and television) and hospitals similar to findings of a review by Ojewusi et.al, (22).…”
Section: Discussionsupporting
confidence: 92%
“…All the respondents in this study were afraid of being diagnosed with breast cancer. These findings were comparable to those of a Maltese screening program which was organized and found that majority of non-attendees were afraid of the result of the screening programme (21). A large portion of the respondents were afraid of being disfigured.…”
Section: Discussionsupporting
confidence: 74%
“…Labrie and colleagues [24] suggested that fear of breast cancer increased the perception of personal risk among women aged 30 -49 years. A recent study performed in Malta suggested that non-adherence to organized MS programs was associated with fear [25]. Similarly, women in our present study who feared the disease might have tended to overestimate numeric risk, estimate comparative risk mainly accurate and fear could also lead to avoidance of MS.…”
Section: Resultssupporting
confidence: 66%
“…Although general barriers to screening by mammography in Malta have been identified in our earlier study [ 19 ], our findings showed that our screening cohort consisted of attendees and non-attendees to the Maltese Breast Screening programme (MBSP); however, we recognised that the MBSP non-attendees consisted of a heterogeneous group of women with diverse reasons for non-attendance. Hence, screening non-attendees were not a single group of non-compliant Maltese women, but consisted clearly of two distinct subgroups: Women, who had obtained a mammogram outside the MBSP, possibly as a self-initiated action or routine check-up [ 15 ] or as part of private breast awareness campaigns, which may have been based on their recognition of susceptibility to BC and high self-efficacy in preventing BC [ 20 ], and ‘Real’ non-attendees i.e.…”
Section: Introductionmentioning
confidence: 73%